Święta czy przeklęta? W poszukiwaniu tożsamości Rusi i Rosji - Lewandowski, Edmund (Zeszyty Wiejskie, 2014)
The Slavic country, Kievan Rus was established by Swedish Vikings who were referred to as the Rus people or Variangans. The tribes who played a significant role in the history of Rus and Russia were the Teutonic peoples and Germans. For seven centuries (882–1598) the country was ruled by princes and tsars coming from the German chief, Rurik. Then for three centuries (1613–1917) the Romanovs ruled the country and for the last 155 years the German Oldenburg dynasty (Holstein-Gottorp). The Russian federation comprises 12.6% of lands, 42.4% of Europe and 28.4% of Asia. This is rather a continent than one of the countries of the world. And the problems they face are also continental . One of the difficult natural challenges is definitely permafrost, which makes up 60% of Russia and 80% of Siberia. The other significant ones include social-political challenges: western (mainly American), Muslim, Far Eastern (mainly Chinese). Russia and the Russians are often associated with the mythical Sphinx which had a face of a woman, breast and paws of a lion, a tail of a snake and wings of an eagle. Thus the face of the nation can be the heroines from Fyodor Dostoyevsky’s novels: Nastasja Filipowna Baraszkow, Agłaja Jepanczyn and Katarzyna, Liza, Achmakowa, Dunia. Their actual prototype was Apolinaria Susłowa. She was best characterized by Wasilij Rozanow. He wrote: „A very Russian type, however, I have never met such a Russian woman in my life. She has something of the Khylst Saint Mother of God or Catherine de Medici. She is wonderful, fascinating, but simultaneously cold-blooded and able to commit a crime. On the St. Bartholomew’s Day she would shoot the Huguenots as a sport”. Nothing more, nothing less…